A Technique For The Direct Measurement Of Bubble Frother Coverage - A. Zangooi (International Mineral Processing Congress, 2012)
Frothers play major roles in flotation through interaction at the air/water interface. A method of determining frother adsorption density (coverage), i.e., the number of molecules per unit of interfacial area of bubble surface, is introduced. The technique is based on mass balancing the frother around a continuously operated bubble column. The mass balance requires collection of bubbles before they burst. The column design and operating procedure is reviewed, and some preliminary results discussed. Keywords: flotation, colorimetric frother analysis technique, frother mass balance, coverage